Mothers’ Awareness on Prevention of Home Accidents among Children in a Community - Kalikotay, Bhagawaty; Rijal, Rabina (Journal of Research and Development, 2022)
Children are at risk for injury because of their normal curiosity, impulsiveness, andesine to master new skills and imitate adult behavior from an early age. Injuries are the first leading but predictable, avoidable and preventable cause of morbidity and mortality among under-five-year-old children worldwide. The objective of the study was to find out the Mothers’ awareness on prevention of home accidents among children in a community. A descriptive cross sectional research design was applied. Study was conducted in community of ward number 8 at Mahalaxmi municipality in Lalitpur district. No probability, purposive sampling technique was used to select 92 mothers of under than five children. Semi structured interview schedule was used to collect the data. The data was entered in SPSS 16 version and was analyzed by both descriptive statistics like frequency, percentage, mean, median, standard deviation and inferential statistics i.e. Chi-Square test. The finding of the study revealed that more than half (58.7%) respondents had good awareness and nearly half (41.3 %) had average awareness on home accidents. This study also showed that the type of family of respondents was significantly associated with level of awareness of respondents (p =0.020). Most of the respondents (83.7%) knew about prevention of home accidents from radio. This study concluded that about half of the mothers had average awareness on prevention of home accidents among children. So, education programmes to mothers of under five children to enhance their knowledge and increase awareness on accident prevention measures through mass media is needful.